2023
DOI: 10.1590/1984-0462/2023/41/2021302
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal near miss and mortality and associated factors: cohort study of births in the city of Rio de Janeiro, RJ, Brazil

Abstract: Objective: The aim of this study was to investigate factors associated with neonatal near miss and mortality of the live birth cohort in the city of Rio de Janeiro, Brazil, in 2015. Methods: Population-based retrospective cohort of live births (LB) of single pregnancy with 0–27 days of follow-up. Data were obtained from the Brazilian Live Birth and Mortality Information Systems. Logistic regressions with the analytical strategy of hierarchical determination were used for cases of near miss and deaths separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 22 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Adolescence and low schooling were more related to fetal growth restriction in full-term infants, corroborating studies in other low- and middle-income countries 37 , 38 . Older maternal age emerged among preterm live births, according to a study in the city of Rio de Janeiro 19 . Black people and inadequate prenatal care were frequent in the extreme combination - preterm SGA - which was an expected result since both are corroborated factors for these conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescence and low schooling were more related to fetal growth restriction in full-term infants, corroborating studies in other low- and middle-income countries 37 , 38 . Older maternal age emerged among preterm live births, according to a study in the city of Rio de Janeiro 19 . Black people and inadequate prenatal care were frequent in the extreme combination - preterm SGA - which was an expected result since both are corroborated factors for these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Eligible newborns had birth weight ≥ 500g, gestational age ≥ 22 weeks, and were children of single pregnancy. Records with values of inconsistent weight for gestational age, that is, values outside the consistent ranges of the lowest 3rd percentile value and the highest 97th percentile value 19 , and with reports of congenital anomalies (10th revision of the International Classification of Diseases - ICD-10 - code described in field 34 of the Declaration of Live Births), were excluded, due to their relationship with birth weight, growth restriction, and prematurity 9 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of previous pregnancies showed that 39.3% (5,191 The analysis of the adequacy of PNC in the RS and in the state's seven health macro-regions following the guidelines of the BMoH (Table 3) showed that, at the state level, 57.5% (n = 7,717, 95%CI: 56.3-58.6) started PNC up to the 12th of pregnancy and had at least six consultations. Also, according to BMoH criteria, the degree of inadequacy of PNC in the state reached 37.6% (n = 5,054, 95%CI: 36.8-38.5), being more expressive in the Metropolitan region (39.2%, n = 2,359, 95%CI: 37.9-40.4) and in the Sierra region (39.1%, n = 570, 95%CI: 36.6-41.6).…”
Section: General Characteristicsmentioning
confidence: 99%
“…Maternal and infant mortalities are associated with the PNC inadequacy [3][4][5] . Therefore, a PNC with early onset and intervention for risk situations, as well as an agile hospital referral system, and the qualification of childbirth care, are the major health determinant indicators related to the mother and the newborn 3,4 .…”
Section: Introductionmentioning
confidence: 99%